2020
DOI: 10.1007/s00277-020-04075-6
|View full text |Cite
|
Sign up to set email alerts
|

LPS-induced expression and release of monocyte tissue factor in patients with haemophilia

Abstract: In haemophilia, thrombin generation and fibrin deposition upon vascular injury critically depend on the tissue factor (TF)-driven coagulation pathway. TF expression by monocytes/macrophages and circulating microvesicles contributes to haemostasis, thrombosis and inflammation. Inflammation is a hallmark of blood-induced joint disease. The aim of this study is to correlate TF production by whole-blood monocytes with inflammatory markers and clinical parameters in patients with moderate-to-severe haemophilia A or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…The extrinsic coagulation cascade can be triggered by soluble or cell-surface CD142 (tissue factor). Prior studies have demonstrated increased CD142 expression in the setting of viral infections (55-58) and in response to LPS (55, 59). In addition, there is a correlation between higher levels of CD142 and COVID-19 disease severity (57, 58).…”
Section: Expression Of Cd142 (Tissue Factor) Is Decreased In Convales...mentioning
confidence: 99%
“…The extrinsic coagulation cascade can be triggered by soluble or cell-surface CD142 (tissue factor). Prior studies have demonstrated increased CD142 expression in the setting of viral infections (55-58) and in response to LPS (55, 59). In addition, there is a correlation between higher levels of CD142 and COVID-19 disease severity (57, 58).…”
Section: Expression Of Cd142 (Tissue Factor) Is Decreased In Convales...mentioning
confidence: 99%
“…The extrinsic coagulation cascade can be triggered by soluble or cell-surface CD142 (tissue factor). Prior studies have demonstrated increased CD142 expression in the setting of viral infections [49][50][51][52] and in response to LPS 49,53 . In addition, there is a correlation between higher levels of CD142 and COVID-19 disease severity 51,52 .…”
Section: Expression Of Cd142 (Tissue Factor) Is Decreased In Convales...mentioning
confidence: 99%
“…Liver cirrhosis patients usually have higher endotoxemia and systemic inflammation due to gut dysbiosis. Endotoxin can increase thrombosis through the production of tissue factor (TF) ( 75 ). With the increase of intestinal permeability and bacterial translocation, the level of LPS in the blood of patients with liver cirrhosis increased significantly.…”
Section: Liver Cirrhosis-related Complications and Dysbiosismentioning
confidence: 99%